Discharge Estimation for Groundwater Basin Fully Delineated Watersheds Based on the Modified Rational Equation - Mayavani, Christine; Soekarno, Indratmo; Farid, Mohammad; Taufiq, Ahmad; Farid Fakhruddin, Muhammad (Civil Engineering Journal, 2026)
The integration of surface water and groundwater is essential for sustainable water resources management, as both components are hydrologically interconnected through runoff, interflow, and baseflow processes. Surface water and groundwater are inseparable components of the hydrological system, contributing significantly to streamflow and to the calculation of water availability in watersheds. A previous study proposed a simpler, improved equation based on a rational method to estimate potential discharge for fully delineated watersheds within a single groundwater basin. Therefore, this study aimed to analyze potential discharge by applying an equation from previous reports with the addition of a beta (β) parameter to enhance performance. The modified rational equation was compared with three existing methods, namely FJ Mock, Sacramento, and NRECA, across six selected watersheds, including Cidanau, Kupang, Kuto, Sampean, Belawan, and Kumai. The results showed that the modified rational equation achieved the highest correlation coefficient and very good RSR classification, except for Kuto and Belawan. This showed that incorporating the β parameter as a baseflow correction factor in the Modified Rational Equation enhanced model accuracy, as indicated by higher correlation and lower RSR values. Optimal β values showed a strong relationship with watersheds-to-groundwater basin area ratio (AWS/AGWB), determined through an iterative process. The modified rational equation performed optimally in small watersheds (<250 km²), with correlation values >60% in catchments like Cidanau, Kupang, and Kuto. However, the accuracy decreased in larger areas, suggesting suitability for small-scale hydrological systems. The enhancement of the modified rational equation using the β parameter showed an alternative method for determining water availability and potential to improve the development of strategic frameworks of water resource management in Indonesia.